An experimental study of the composition for medicament corneal crosslinking as a promising means for keratoconus treatment - E. N. Iomdina; A. R. Korigodsky; I. P. Khoroshilova-Maslova; L. D. Andreeva; N. Yu. Ignatieva (Российский офтальмологический журнал, 2018)
The deterioration of the corneal framing function in keratoconus is largely due to the dystrophic process and the decrease of collagen structures crosslinking level. The purpose of the study is to perform a preclinical placebo controlled study of the safeness and effectiveness of Cornetex compound instillations for medicament corneal crosslinking. Material and methods. The study included 37 Chinchilla rabbits (74 eyes). 33 rabbits received Cornetex solution instillations into one eye twice a day for 1 month (17 rabbits, 1st series) and for 3 months (16 rabbits, 2nd series). The active constituents of Cornetex include a complex of the basic amino acid salts in the form of succinates (residues of succinate acid) participating in collagen crosslinking formation. The placebo solution containing nonactive Cornetex constituents (Hydroxyethyl cellulose, benzalkonium chloride and water for injections) was instilled into fellow eyes. 4 fully intact rabbits (8 eyes) served as an independent control group. In vivo methods included biomicroscopy and examination with a Scheimpflug camera Galilei G2. 1 and 3 months after the instillation course, the eyes were enucleated and subjected to a morphological study, biomechanical testing of corneal samples (on the testing machine Autograph AGS-H). Corneal collagen crosslinking level was determined by differential scanning calorimetry using a Phoenix DSC 204 calorimeter. Results. Biomicroscopic and morphological studies revealed no pathological changes of ocular media and tissues. One month after the instillation course, the collagen crosslinking level of the cornea showed a 18 to 20 % increase, while its elasticity modulus showed a 1.8-fold increase with respect to the fellow eye, which is an evidence of the safety and high corneal reinforcement effect of the instillations. Conclusions. The outcome of the experimental study of Cornetex implies that it can be recommended for further clinical studies as a promising means for keratoconus treatment. For citations: Iomdina E.N., Korigodsky A.R., Khoroshilova-Maslova I.P., Andreeva L.D., Ignatieva N.Yu. An experimental study of the composition for medicament corneal crosslinking as a promising means for keratoconus treatment. Russian ophthalmological journal. 2017; 10 (4): 54-61. doi: 10.21516/2072-0076-2017-10-4-54-61 (In Russian).